Peran ESG dalam keuangan hijau: Pemetaan bibliometrik global - Azam Asykarulloh; Muh Syaiful Bakhri; Muhammad Isbad Addainuri (Nur Science Institute, 2026)
The study maps the developments, trends, and directions of global research in Environmental, Social, and Governance (ESG) and Green Finance during the period 2018–2025. This study uses a quantitative bibliometric approach to analyze 573 publications indexed in the Scopus database, identified by title, abstract, and keywords. The data are processed using the Bibliometrix software (R package). The analysis was carried out through several bibliometric techniques, including analysis of publication performance (annual growth, sources, and productive countries), keyword and co-occurrence analysis to identify conceptual structures, topic trend analysis to map research dynamics, and analysis of author and country collaboration to describe global scientific networks. The results show that ESG and Green Finance-related publications experienced significant growth, with an annual growth rate of 51.86%. The three most dominant themes are green finance, ESG, and sustainable development. China is emerging as a leading country in both publication output and international collaboration. In addition, the study identified several research gaps, including limited empirical evidence from developing countries, inconsistencies in ESG assessment indicators, and a lack of studies on real environmental impacts.